COVID-19 vaccine adoption and hesitancy among older Veterans - Tamar Wyte-Lake; Cari Levy; Sona Hovsepian; Yvonne Mudoh; Cheryl Schmitz; Aram Dobalian (BMC, 2022)
Abstract Background Older adults are particularly at risk for severe illness or death from COVID-19. Accordingly, the Veterans Health Administration (VA) has prioritized this population group in its COVID-19 vaccination strategy. This study examines the receptivity of Veterans enrolled in the VA's Geriatric Patient Aligned Care Team (GeriPACT) to receiving the COVID-19 vaccine. GeriPACT is an outpatient primary care program that utilizes multi-disciplinary teams to provide health services to older Veterans. Methods We conducted semistructured interviews with 42 GeriPACT-enrolled Veterans from five states. Participants were asked to identify barriers to vaccine acceptance. We gathered data from January-March 2021 and analyzed them using qualitative methods. Results Both White and African American GeriPACT Veterans had minimal vaccine hesitancy towards the COVID-19 vaccine. On-line registration and ineligibility of a spouse/caregiver for vaccination were primary barriers to early vaccination. Conclusions As the first wave of early adopters of the COVID-19 vaccination effort nears completion, targeted strategies are needed to understand and respond to vaccine hesitancy to lower the risk of subsequent waves of infections. The 2021 SAVE LIVES Act, begins to address identified vaccination barriers by permitting vaccination of Veteran spouses and caregivers, but consideration must be given to creating alternatives to on-line registration and allowing spouses and caregivers to register for appointments together.